2014
DOI: 10.5121/ijcsit.2014.6103
|View full text |Cite
|
Sign up to set email alerts
|

Information Security Risk Analysis Methods and Research Trends: AHP and Fuzzy Comprehensive Method

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 31 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…Additionally, this literature research has revealed that there is a trend of developing hybrid models for risk analysis and assessment, and for deciding on the state of security or choosing an appropriate information system by using multicriteria decision-making (specifically indicated in the studies [38,43]), which is actually a logical phenomenon of interdisciplinarity in conducting researches as information security risk management is necessarily integrated into other business domains, and thus becoming one of the top priority activities in protecting the assets and operations of each modern organization.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, this literature research has revealed that there is a trend of developing hybrid models for risk analysis and assessment, and for deciding on the state of security or choosing an appropriate information system by using multicriteria decision-making (specifically indicated in the studies [38,43]), which is actually a logical phenomenon of interdisciplinarity in conducting researches as information security risk management is necessarily integrated into other business domains, and thus becoming one of the top priority activities in protecting the assets and operations of each modern organization.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Also, the AHP model for classification of information assets is presented, taking into account the already mentioned risk assessment factors as evaluation criteria, but the paper does not specify to which exact information systems the proposed model would be applied and no necessary (inherent) interdependencies defined between risk assessment factors (which is actually a drawback of the AHP itself). Lee [43] proposes identical risk analysis factors as in the paper [42], except that for each of the 4 criteria in the AHP certain additional sub-criteria are also defined. E.g.…”
Section: Analysis Of Papersmentioning
confidence: 99%
See 1 more Smart Citation
“…More generally, this is a multicriteria decision-making (MCDM) problem, and a review of the literature highlights a significant application of MCDM in the context of risk assessment, as well as a need for a new hybrid model with the integration of information security elements [37]. There is a trend of research in hybrid models for risk analysis and assessment [38,39], implying interdisciplinarity in conducting researches, and consequently integration with other business domains.…”
Section: Information Security Elements In Service Sciencementioning
confidence: 99%
“…For example, Ming-Chang Lee has used sets during management of security risk. 24 Dark et al 25 have applied the fuzzy set theory that evaluates the cost and time performance, security risk management and utilization of healthcare web application development scheme. Shedden et al 26 utilized the structure of security risk for qualitative assessment of security risk of healthcare web application.…”
Section: Related Workmentioning
confidence: 99%